Comprehensive Load Regulation Strategy Considering Outage Risk in Power Tight Balance Scenarios - Shunjiang Wang; Zhongwei Li; Rongmao Wang; Huan Ma (IEEE Access)
With the steadily growing penetration of renewable energy, considerable uncertainties and intermittency are introduced to the power grid. On the other hand, controllable load plays an increasingly important role in the system power balance. Therefore, load regulation strategy is more critical than before to the reliability and safety of power system. A framework of comprehensive load regulation strategy with consideration of outage risk is proposed in this work to deal with power tight balance and power deficiency. Firstly, the orderly electricity consumption (OEC) and demand response (DR) based on time of use (TOU) pricing program are collaboratively employed. Then, orderly consumption power (OCP) is determined by power balance analyzing and flexible resource accessing, reasonably allocated over the subsystems by considering the load types and energy efficiencies, and further specified by components of peak shifting, peak averting and power rationing. Secondly, load-shedding risk evaluation algorithm based on multiple samplings with short-term chronological sequences (MSSCS) is proposed to accurately evaluate load-shedding risk without prohibitive computational burdens. Furthermore, the clear pictures of outage risks over OCP are depicted by calculating incremental cost-effectiveness ratios. Comprehensive case studies are implemented and confirm the validity of the proposed methodology.